Extending a virtual chemistry laboratory with a collaboration script to promote conceptual learning. (28th January 2010) - Tsovaltzi, Dimitra; Rummel, Nikol; McLaren, Bruce M.; Pinkwart, Niels; Scheuer, Oliver; Harrer, Andreas; Braun, Isabel
We developed collaborative extensions to 'Vlab', a web-based laboratory that supports students in conducting virtual chemistry experiments. While results from a recent study indicated that VLab promotes chemistry learning, they also revealed that there is room for improvement. We embedded VLab into a collaborative environment that implements a computer-supported collaboration script for guiding students through the stages of scientific experimentation. We describe our pedagogical approach, our collaboration script, and the collaborative learning environment which implements it. We present results from two small-scale studies and a contrasting-case analysis of how adaptive prompts, in addition to the fixed script, affected student behaviour.